Whole-Exome Sequencing Identified Novel CLMP Mutations in a Family With Congenital Short Bowel Syndrome Presenting Differently in Two Probands - Chuang, Yao-Hung; Fan, Wen-Lang; Chu, Yu-De; Liang, Kung-Hao; Yeh, Yuan-Ming; Chen, Chien-Chang; Chiu, Cheng-Hsun; Lai, Ming-Wei (Frontiers in Genetics, 2020)
Congenital short bowel syndrome (CSBS) is a rare condition characterized by an inborn shortening of bowel length with loss of intestinal functions, which often combines malrotation. CXADR-like membrane protein (CLMP) and filamin A (FLNA) gene mutations are the two major causes of this inherited defect. We presented two siblings with the older brother suffering from a laparotomy for bowel obstruction due to malrotation on the 17th day after birth. The younger sister encountered a laparotomy for lactobezoar at 6 months old. CSBS was diagnosed by measurement of the bowel length during the operations. Compound heterozygous CLMP mutations with the paternal allele harboring a long deletion across exon 3–5 and the maternal allele bearing a non-sense mutation of exon 3 (c.235C > T, p.Q79∗) were identified in both cases. They are the first reported familial CSBS caused by novel CLMP mutations in Taiwan.